PENGARUH KURANGNYA PERHATIAN ORANG TUA TERHADAP PERKEMBANGAN BELAJAR SISWA KELAS 1 SD - Lisna Amelia (Pusat Riset dan Inovasi Nasional, 2023)
Abstract. One of the causes of the less than optimal development of student learning is the influence of the lack of attention from parents on student learning at home. The attention of parents is very important and influential for the smooth development of student learning both at home and at school. The busyness of parents at work can have an influence on the development of children's learning, where time together with children will be reduced. This study aims to find out how the influence of the lack of attention of parents on the learning development of 1st grade students. In this study, researchers used descriptive qualitative research methods. Where researchers use data sources obtained through interviews and from the results of literature studies from various reference sources such as journals, books, and articles. The results of the study show that optimal children's learning development can be carried out if there is full awareness in giving attention and not giving negative judgments about children's behavior. Where both parents must pay more attention by accepting and not judging the child. Keywords: Parental attention, Children's Learning Development. Abstrak. Perkembangan belajar siswa yang kurang optimal salah satunya disebabkan karena adanya pengaruh kurang perhatian dari kedua orang tua terhadap belajar siswa dirumah. Perhatian kedua orang tua sangat peting dan berpengaruh bagi kelancaran perkembangan belajar siswa baik di sekolah ataupun di rumah. Kesibukan orang tua dalam bekarja mampu memberikan pengaruh bagi perkembangan belajar anak, dimana waktu kebersamaan dengan anak akan berkurang. Penelitian ini bertujuan untuk mengetahui bagimana pengaruh kurangnya perhatian orang tua terhadap perkembangan belajar siswa kelas 1 SD. Pada penelitian ini peneliti menggunakan metode penelitian secara kualitatif deskriptif. Dimana peneliti menggunakan sumber data yang diperolah melalui hasil wawancara dan dari hasil studi kepustakaan dari berbagai sumber referensi seperti jurnal, buku, dan artikel. Hasil penelitian menunjukkan bahwa perkembangan belajar anak yang optimal dapat dilakukan apabila adanya kesadaran penuh dalam memberikan perhatian dan tidak memberikan penilaian negatif terhadap perilaku anak. Dimana kedua orang tua harus lebih memperhatikan dengan menerima dan tidak menghakimi anak. Kata kunci: Perhatian orang tua, Perkembangan Belajar Anak.